“Leaky Bucket” of Kazakhstan’s Power Grid: Losses and Inefficient Distribution of Electric Power - Emil Velinov; Yelena Petrenko; Elena Vechkinzova; Igor Denisov; Luis Ochoa Siguencia; Zofia Gródek-Szostak (Energies, 2020)
This paper aims to determine and explain the main factors for power losses (the so-called “leaky bucket” effect) in Kazakhstan and the reasons for inefficient energy distribution within the country. Energy efficiency in Kazakhstan is much lower compared to more economically developed countries. The differences between energy efficiency in various regions of Kazakhstan are also significant. This article explores the impact of administrative monopoly tariffs on the regional energy efficiency, based on a national study conducted in Kazakhstan in 2017. The purpose of the study was to identify the administrative barriers and their impact on the sustainability of enterprise development. What hinders the distribution of energy resources among different regions is artificial barriers in the energy market and the administrative tariff monopoly for electric power. This leads to the inefficient distribution of resources throughout the country. In addition, it is difficult to leverage low distribution efficiency in the absence of a market. The authors attempt to prove that the magnitude of administrative barriers directly affects the efficiency and competitiveness of business, as well as the final prices of goods and services for the end consumer.